Personalized Learning: Empowering a Student with Autism Spectrum Disorder in Basic Grammar Course - Lemmuela Alvita Kurniawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This paper provides illustrations of how a personalized learning approach is implemented in the Basic Grammar course to empower a student with an autism spectrum disorder is taking the ownership of learning and meeting his learning needs based on his strengths, weaknesses, and interests. Building upon literature and pedagogical practices of personalized learning, this paper details the innovations implemented in the Basic Grammar course for a student with an autism spectrum disorder to take more control of his learning, facilitate decision-making and communication skills, and engage in the learning process. Additionally, the innovations implemented in this course mirror the essence and principles of personalized learning. This paper is expected to enrich educators in the attempts to adopt a personalized learning approach and to give new insight into how to implement personalized learning in an inclusive classroom. Moreover, it is hoped that the idea of equity in inclusive education by implementing personalized learning could be an omnipresent practice to improve the quality of education for all in Indonesia.